PENANGANAN DISPEPSIA PADA LANJUT USIA - Wibawa, I Dewa Nyoman (journal of internal medicine, 2006)
In elderly patients with dyspeptic syndrome, organic causes more prevalence rather than fungsional related disorders. Theuse of Nonsteroid Anti Inflammatory Drugs (NSAIDs) and H. pylori infection play as important role as causes of organicdyspepsia in eldery patients. There are some changes in upper gastrointestinal tract which is related to aging process, especially inmucosal defance mechanism. The changes in aggressive factors are only a few. Diagnostic approach with endoscopic examinationis necessary in eldery patients with dyspeptic syndrome to role out the possibility of organic origin. The management of dyspepsiain eldery patients needs comprehensive approach because clinical presentation usually asymptomatic, the use of polypharmacy,co-morbidity, and the probability of organic origin as a cause needs to be proved since the beginning.